Modeling of a novel biosensor with integrated mass and electrochemical sensing capabilities - Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin; Ab Rahim, Rosminazuin; Mak, Wing Cheung (IEEE, 2017)
Rapid development in technology and society has generated diverse developments in many fields including biosensors in healthcare application. Here, the design of integrated biosensor comprises mass sensing (Quartz Crystal Microbalance) and electrochemistry sensing (Electrochemical Impedance Spectroscopy, EIS and Cyclic Voltammetry, CV) will be presented. The integrated sensor system is developed based on the innovative use of the top electrode of a quartz crystal microbalance (QCM) resonator as a working electrode for the electrochemistry technique. Integration of QCM with the electrochemistry technique is realized by fabricating a semicircular counter electrode near the upper electrode on the same side of the quartz crystal. CV and EIS measurement was conducted using finite element modeling, COMSOLTM 5.2 with the probe marker of 1 mmol L−1 of [Fe(CN)6]3−/4−. CV test was done to study the effect between increasing scan rate and peak current (anodic and cathodic) in observing the reversible electrochemical process. This observation is crucial in ensuring the electrochemical processes follow the Randles-Sevcik equation in characterizing the platform changes behavior. Later, EIS test was performed in order to measure the radius of the semicircle which reflects the charge transfer resistance (RCT) of the redox marker. To show the effectiveness of this sensor, gold immobilization surface was electrochemically simulated and reported. Thus, an ultra-sensitive biosensor that capable to produce multi-analysis in the detection of biological targets in terms of electrochemical change of electrode interfaces, which is the crucial step towards the engineering of advanced bioelectronics.